Effect of Simulated Soil Solarization and Organic Amendments on Fusarium Wilt of Rocket and Basil Under Controlled Conditions. Issue 9 (9th January 2014) - Gilardi, Giovanna; Demarchi, Stefano; Gullino, Maria Lodovica; Garibaldi, Angelo
Abstract Pot trials were carried out under controlled conditions to evaluate the effectiveness against Fusarium wilt of rocket (Fusarium oxysporum f.sp. conglutinans) and basil (F. oxysporum f.sp. basilici) of soil amendments based on a patented formulation of Brassica carinata defatted seed meal and compost, combined or not with a simulation of soil solarization. The soil solarization treatment was carried out in a growth chamber by heating the soil for 7 and 14 days at optimal (55–52°C for 6 h, 50–48°C for 8 h and 47–45°C for 10 h/day) and sub‐optimal (50–48°C for 6 h, 45–43°C for 8 h and 40–38°C for 10 h/day) temperatures similar to those observed in summer in solarized soil in greenhouses in Northern Italy. Two subsequent cycles of plant cultivation were carried out in the same soil. Even at sub‐optimal temperature regimes, 7 days of thermal treatment provided very valuable results in terms of disease control on both rocket and basil. In general, the thermal treatment was more effective against F. oxysporum f.sp. basilici than against F. oxysporum f.sp. conglutinans. Control of Fusarium wilt of rocket is improved with 14 days of thermal treatment. The combination of organic amendments with a short period of soil solarization (7 or 14 days), although not providing any improvement to the level of disease management, did significantly increase biomass and positively affected yield.